A strontium isoscape of southwestern Australia and progress toward a national strontium isoscape - P. de Caritat; P. de Caritat; A. Dosseto; F. Dux (Earth System Science Data)
Strontium isotopes (87Sr/86Sr<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="7f4baae305f328d12fa7f61ee32c1202"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-17-79-2025-ie00001.svg" width="49pt" height="15pt" src="essd-17-79-2025-ie00001.png"/></svg:svg>) are widely used tracers in the geosciences. Here we exploit an opportunity to determine 87Sr/86Sr<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="fc572d0bea75b4287a5b3ee79eca9f85"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-17-79-2025-ie00002.svg" width="49pt" height="15pt" src="essd-17-79-2025-ie00002.png"/></svg:svg> ratios on archived fluvial sediment samples from the low-density National Geochemical Survey of Australia (NGSA). The present study targeted the Yilgarn Craton in southwestern Australia. In total, 107 samples were taken from a depth of ∼ 60–80 cm in floodplain deposits at or near the outlet of large catchments (drainage basins). A coarse (< 2 mm) grain-size fraction was air-dried, sieved, milled, and then digested (hydrofluoric acid and nitric acid, followed by aqua regia) to release total Sr. The Sr was then separated by chromatography and its 87Sr/86Sr<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="e22ae2ee47cc1ea64b1ec348ae40208d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-17-79-2025-ie00003.svg" width="49pt" height="15pt" src="essd-17-79-2025-ie00003.png"/></svg:svg> ratio determined by multicollector inductively coupled plasma mass spectrometry (MC-ICP-MS). Results demonstrate a wide range of quite elevated Sr isotopic values (0.7152 to 1.0909, with a median of 0.7560) over the survey area, reflecting a large diversity of source rock lithologies, geological processes, and bedrock ages. The spatial distribution of 87Sr/86Sr<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="a97dd5d5ad53911d125562a9ee29d24d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-17-79-2025-ie00004.svg" width="49pt" height="15pt" src="essd-17-79-2025-ie00004.png"/></svg:svg> shows coherent (multi-point anomalies and smooth gradients) large-scale (> 100 km) patterns that appear to be broadly consistent with surface geology, regolith/soil type, and/or nearby outcropping bedrock. The most radiogenic sediment values in the Yilgarn region (87Sr/86Sr<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="5260b111447fe6189885d1843a512fbf"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-17-79-2025-ie00005.svg" width="49pt" height="15pt" src="essd-17-79-2025-ie00005.png"/></svg:svg> > 0.8) all come from sites underlain by Archaean bedrock (2500–4000 Ma) and almost exclusively felsic intrusive lithologies. Conversely, almost all sites underlain by younger and non-granitic bedrock have outlet sediments of a less radiogenic character (87Sr/86Sr<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="395bd4779ea7edb24c266694c8e7734d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-17-79-2025-ie00006.svg" width="49pt" height="15pt" src="essd-17-79-2025-ie00006.png"/></svg:svg> < 0.8). Sampling sites underlain by mafic and ultramafic bedrock yield unradiogenic Sr sediment signatures despite their Archaean age. Several sediment 87Sr/86Sr<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="25a89f7d431e088bd307521c30406ca6"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-17-79-2025-ie00007.svg" width="49pt" height="15pt" src="essd-17-79-2025-ie00007.png"/></svg:svg> results were validated by comparison to previously published whole-rock data from their catchment for both unradiogenic and radiogenic cases. The new Sr isotopic data are also interrogated in terms of the mineral occurrences (i.e. mineral deposits and/or operating mines) found in their catchment. Several catchments containing mineral resources across a range of commodities stand out as high-87Sr/86Sr<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="fef97a353234dc7f2e8249054738748d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-17-79-2025-ie00008.svg" width="49pt" height="15pt" src="essd-17-79-2025-ie00008.png"/></svg:svg> outliers (87Sr/86Sr<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="b15b20bdf743f7fd52e15b626449e320"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-17-79-2025-ie00009.svg" width="49pt" height="15pt" src="essd-17-79-2025-ie00009.png"/></svg:svg> > 0.8), whilst over half of the registered mineral resources come from an intermediate, yet still elevated, catchment sediment 87Sr/86Sr<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="d84d9178998f432e013c66f081dd664b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-17-79-2025-ie00010.svg" width="49pt" height="15pt" src="essd-17-79-2025-ie00010.png"/></svg:svg> range (87Sr/86Sr<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="f05f1fcb7ddd0bc765b0b1cada09fe9b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-17-79-2025-ie00011.svg" width="49pt" height="15pt" src="essd-17-79-2025-ie00011.png"/></svg:svg> = 0.728–0.767). Avenues for future work are proposed, including a national-scale Sr isoscape for Australia. Such an isoscape could be useful in future geological, forensic, archaeological, palaeontological, and ecological studies. The new spatial Sr isotope dataset for the southwestern Australia region is publicly available (de Caritat et al., 2024; https://doi.org/10.26186/149755).